Emotion information processing as a new component of emotional intelligence: Theoretical framework and empirical evidence. Issue 2 (March 2022) - Fiori, Marina; Udayar, Shagini; Vesely Maillefer, Ashley
The relationship between emotional intelligence (EI) and emotion information processing (EIP ) has received surprisingly little attention in the literature. The present research addresses these gaps in the literature by introducing a conceptualization of emotional intelligence as composed of two distinct components: (1) EIK or emotion Knowledge component, captured by current ability emotional intelligence tests, related to top-down, higher order reasoning about emotions, and which depends more strongly on acquired and culture-bound knowledge about emotions; (2) EIP or emotion information Processing component, measured with emotion information processing tasks, requires faster processing and is based on bottom-up attention-related responses to emotion information. In Study 1 ( N  = 349) we tested the factorial structure of this new EIP component within the nomological network of intelligence and current ability emotional intelligence. In Study 2 ( N =111) we tested the incremental validity of EIP in predicting both overall performance and the charisma of a presenter while presenting in a stressful situation. Results support the importance of acknowledging the role of emotion information processing in the emotional intelligence literature and point to the utility of introducing a new EI measure that would capture stable individual differences in how individuals process emotion information.